1997
DOI: 10.1139/z97-791
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent foraging behaviour and use of cover in juvenile coho salmon under predation risk

Abstract: Foraging and use of cover by juvenile coho salmon (Oncorhynchus kisutch) were affected by predation threat in both seminatural channels and laboratory streams. In the field, coho salmon preferred stream sections with brushy cover only when under threat from hunting common mergansers. The mergansers had their highest capture success in pools without cover. Predation threat also caused coho salmon to use cover more as foraging habitat and to aggregate more in favourable positions at the head of the pool. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
0
37
3
Order By: Relevance
“…This type of size-based hierarchical behavior in terms of occupying preferable habitats has been demonstrated for stream-dwelling juveniles of brown trout (Salmo trutta) (Elliot 1990(Elliot , 1994. Reinhardt and Healey (1997) proposed a similar mechanism to explain size-related, differential habitat usage by coho salmon (Oncorhynchus kisutch). They suggested that in the presence of predators, larger fish were more risk averse than smaller fish, which occupied energetically more favorable but riskier habitats.…”
Section: Discussionmentioning
confidence: 99%
“…This type of size-based hierarchical behavior in terms of occupying preferable habitats has been demonstrated for stream-dwelling juveniles of brown trout (Salmo trutta) (Elliot 1990(Elliot , 1994. Reinhardt and Healey (1997) proposed a similar mechanism to explain size-related, differential habitat usage by coho salmon (Oncorhynchus kisutch). They suggested that in the presence of predators, larger fish were more risk averse than smaller fish, which occupied energetically more favorable but riskier habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Age-1 steelhead show much stronger preference for deeper pools and cover than age-0 steelhead Chapman 1972, Bisson et al 1988). Whether young steelhead reared in the two treatments would develop different affinities for cover in the stream as they grow older, or under the threat of predators Godin 1991, Reinhardt andHealey 1997) remains to be tested. Conservation hatcheries for maintaining or restoring populations of salmonids have the option to restock hatchery-reared offspring into their ancestral habitats at various life history stages, for example, eyed egg, age-0, age-1, or smolt.…”
Section: Discussionmentioning
confidence: 99%
“…(2002) 365/366 : 297-324 the highest risk of predation in shallow habitats is for large fish, due to non-gape limited predators (birds and mammals) whereas in deeper habitats it is for small fish from gapelimited, piscivorous fish (POWER, 1987;SCHLOSSER, 1987). Some laboratory and field experimental studies have clearly demonstrated that terrestrial predation risk from wading/diving animals is much higher for water-column species in shallow pools than in deep pools and added cover markedly increases their survival (HARVEY and STEWART, 1991;LONZARICH and QUINN, 1995;REINHARDT and HEALEY, 1997). Hence, beyond physical structures that provide shelter from predators, water depth heterogeneity constitutes an essential cover feature regulating predator-prey interactions.…”
Section: Predationmentioning
confidence: 99%
“…Several studies have shown that small fish taxa increased cover use in the presence of fish predators (WERNER et al, 1983b;HUNTINGFORD et al, 1988a;RAHEL and STEIN, 1988; and bird predators (HOLIERHOEK and POWER, 1995;REINHARDT and HEALEY, 1997) or remained in risky sites only if those sites were structurally complex (FRASER and CERRI, 1982). The underlying mechanisms of the reduction in predator foraging success included a limitation of manoeuvrability of predators, a reduction in visual contacts, and an increase in evasive abilities of prey (HELFMAN, 1981).…”
Section: Predationmentioning
confidence: 99%
See 1 more Smart Citation